2016
DOI: 10.1523/jneurosci.4109-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Panic Anxiety in Humans with Bilateral Amygdala Lesions: Pharmacological Induction via Cardiorespiratory Interoceptive Pathways

Abstract: We previously demonstrated that carbon dioxide inhalation could induce panic anxiety in a group of rare lesion patients with focal bilateral amygdala damage. To further elucidate the amygdala-independent mechanisms leading to aversive emotional experiences, we retested two of these patients (B.G. and A.M.) to examine whether triggering palpitations and dyspnea via stimulation of nonchemosensory interoceptive channels would be sufficient to elicit panic anxiety. Participants rated their affective and sensory ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 70 publications
0
51
0
Order By: Relevance
“…57 Remarkably, findings of greater amygdala activation in patients with panic disorder than in healthy controls are inconsistent, 9,58 and panic attacks have even been observed in patients with amygdala lesions. [59][60][61] Thus, the amygdala seems to be associated with relevance detection and salience processing, 62,63 initiating a cascade of panic-related activations without being necessarily involved in (all) full-blown panic attacks. 60 The thalamus, as a sensory relay station, is important for the fast processing of incoming visual input and weighing its relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Remarkably, findings of greater amygdala activation in patients with panic disorder than in healthy controls are inconsistent, 9,58 and panic attacks have even been observed in patients with amygdala lesions. [59][60][61] Thus, the amygdala seems to be associated with relevance detection and salience processing, 62,63 initiating a cascade of panic-related activations without being necessarily involved in (all) full-blown panic attacks. 60 The thalamus, as a sensory relay station, is important for the fast processing of incoming visual input and weighing its relevance.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] Thus, the amygdala seems to be associated with relevance detection and salience processing, 62,63 initiating a cascade of panic-related activations without being necessarily involved in (all) full-blown panic attacks. 60 The thalamus, as a sensory relay station, is important for the fast processing of incoming visual input and weighing its relevance. Its activation is modulated by selective attention, which gains special significance in the present study owing to the task-irrelevance of panic-related stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…During each task scan, participants received a single bolus intravenous infusion at 60 seconds while lying in the scanner: either saline or isoproterenol hydrochloride (Valeant Pharmaceuticals, Laval, Quebec, Canada), at a dose of 1 microgram (μg) or 2 μg. We selected these bolus doses because (i) they produced sizeable and reliable changes in cardiorespiratory parameters in our previous studies (Khalsa, et al, 2016; Khalsa, et al, 2009a; Khalsa, et al, 2009b), (ii) we have found them to be well tolerated in the fMRI environment (Hassanpour, et al, 2016), and (iii) they induce transient changes lasting <100 seconds, so that we can expect their effects do not extend to subsequent scans. Each dose was repeated twice for a total of six infusion scans, and the infusion order was randomized and double-blinded (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Isoproterenol is a rapidly acting beta-adrenergic medication that is similar to adrenaline. It acts by peripherally stimulating cardiorespiratory output (Khalsa, et al, 2016; Khalsa, et al, 2009a; Khalsa, et al, 2009b). It does not cross the blood brain barrier (Murphy and Johanson, 1985; Olesen, et al, 1978), and we have recently demonstrated that this medication is amenable to identifying neurocognitive functions in the fMRI environment (Hassanpour, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This may be one mechanism by which vagal nerve stimulation has its effects [233]. Additional novel approaches to increasing the SNR on interoceptive signals are also under development, including pharmacological interventions such as infusion regimens with the b-adrenoreceptor agonist isoproterenol that have been tested in other psychiatric illnesses [234,235] and therapy within sensory-attenuated environments that increase the salience of interoceptive signals [236].…”
Section: Implications For Treatmentmentioning
confidence: 99%